2018
DOI: 10.1039/c7ra12334e
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted Article: Effect of temperature and large guest molecules on the C–H symmetric stretching vibrational frequencies of methane in structure H and I clathrate hydrates

Abstract: Large molecules such as 2-methylbutane (C 5 H 12 ) or 2,2-dimethylbutane (C 6 H 14 ) form structure H (sH) hydrates with methane (CH 4 ) as a help gas. In this study, the Raman spectra of the C-H symmetric stretch region of CH 4 enclathrated within various sH hydrates and structure I CH 4 hydrates were analyzed in the temperature range 83-183 K. Thermal expansions of these sH hydrate samples were also measured using powder X-ray diffraction. Symmetric stretch vibrational frequencies of CH 4 in host water cages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…The thermal lattice expansions of the sH hydrates hosting CH 4 and halogenic cyclohexanes (ClCH, ICH, and BrCH) were observed by PXRD measurements as the temperature increased from 83 to 183 K. The lattice expansions during temperature ramping are plotted in Figure . The lattice constants linearly increased with temperature, as reported for other clathrate hydrates. , The lattice expansions of the sH hydrates were anisotropic along the a - and c -axes . Such anisotropic behavior originates from the size of the help guest .…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The thermal lattice expansions of the sH hydrates hosting CH 4 and halogenic cyclohexanes (ClCH, ICH, and BrCH) were observed by PXRD measurements as the temperature increased from 83 to 183 K. The lattice expansions during temperature ramping are plotted in Figure . The lattice constants linearly increased with temperature, as reported for other clathrate hydrates. , The lattice expansions of the sH hydrates were anisotropic along the a - and c -axes . Such anisotropic behavior originates from the size of the help guest .…”
Section: Resultssupporting
confidence: 67%
“…Fuseya et al demonstrated a shift toward higher wavenumbers in the C–H peak of CH 4 in sI hydrate and the composite one C–H peak in sH hydrates during temperature ramping. Meanwhile, the peaks in the spectra of sH hydrates cannot be spectrally resolved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooperative relationship between the O–H stretching mode and the O:H stretching phonon in ice or the THF hydrate system has been reported in previous studies. , During the annealing process, the intermolecular hydrogen bonding of the hydrate cage is lengthened and softened with lattice expansion, showing a red shift, and the intramolecular covalent bonding is shortened and stiffened, showing a blue shift. Also, Fuseya et al reported the effects of hydrate cage size on the shift of C–H stretching mode when the temperature increases . The slight blue shift of C–H stretching mode in Figure is similar to the results of the aforementioned study, but there was no significant difference depending on the type of guest molecules.…”
Section: Resultssupporting
confidence: 78%